Distribusi Kepemilikan Lahan Pertanian Dan Pendapatan Usahatani Di Wilayah Perkotaan Kabupaten Jember - Pravitasari Anjar Pratiwi; Mohammad Rondhi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
Conversion of agricultural land to non-agricultural becomes unavoidable, given the high demand for land use to promote economic development. Conversion of agricultural land mostly occurs in urban areas affecting the changing patterns and distribution of agricultural land tenure in urban areas. Higher rents for land in urban areas will trigger land conversion and lead to imbalances in agricultural land tenure. Changes in the distribution of agricultural land will affect farm income, because agricultural land is a valuable asset for farmers and affects their farm income. The purpose of this study was to determine the inequality of agricultural land tenure and farm income in urban areas of Jember. Using analytical method with gini index and descriptive method. Samples were determined by simple random sampling and 43 samples were obtained. The result of the research shows that: (1) land tenure index of agricultural land is 0.52 which means that farm ownership in Jember urban areas is unequal, (2) farm income with gini index 0.46 means that income of farming activity in urban area is uneven.